TACHYARRHYTHMIA AMONG CHILDREN WITH CORRECTED CONGENITAL HEART DISEASE: DIAGNOSTICS AND TREATMENT APPROACHES - I.A. Kovalev; S.V. Popov; G.P. Filippov (Вопросы современной педиатрии, 2006)
At present, one of the most urgent issues in children's cardiology is the problem of tachyarrhythmia among patients, who have undergone the operation for congenital heart diseases. The overview generalizes the information on the diagnostics and treatment of supraventricular and ventricular arrhythmias in early post operation period and within long terms after congenital heart disease correction. The authors examined opportunities for the endocardiac radio frequency ablation and implantation of cardioverters defibrillators in treatment of arrhythmias and prevention of oxymortia.Key words: heart rhythm disturbance, treatment, congenital heart diseases, children.